Bernstein Type Inequalities for Polar Derivative of Polynomial - Chanam, Barchand (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
If is a polynomial of degree n such that in , , then Govil [ Proc. Nat. Acad. Sci., Vol. 50, pp. 50-52, 1980. ] proved provided and attain their maxima at the same point on the circle , where . Equality in the above inequality holds for. In this paper, we extend the above inequality and an improved version of this into polar derivative of a polynomial.